Robust RF shimming and small‐tip‐angle multispoke pulse design with finite‐difference regularization. Issue 3 (1st May 2021) - Paez, Adrian; Gu, Chunming; Cao, Zhipeng
Abstract : Purpose: A new regularizer is proposed for the magnitude least‐squares optimization algorithm, to ensure robust parallel transmit RF shimming and small‐tip‐angle multispoke pulse designs for ultrahigh‐field MRI. Methods: A finite‐difference regularization term is activated as an additional regularizer in the iterative magnitude‐least‐squares based pulse design algorithm when an unwanted flip angle null distribution is detected. Both simulated and experimental B 1 + maps from different transmit arrays and different human subjects at 7 T were used to evaluate the proposed algorithm. The algorithm was further demonstrated in experiment with dynamic multislice RF shimming for a single‐shot gradient‐echo EPI for human functional MRI at 7 T. Results: The proposed finite‐difference regularizer effectively prevented excitation null to be formed for RF shimming and small‐tip‐angle multispoke pulses, and improved the latter with a monotonic trade‐off relationship between flip angle error and RF power. The proposed algorithm was demonstrated to be effective with several head‐array geometries by simulation and with a commercial head array with 12 healthy human subjects by experiment. During a functional MRI scan at 7 T with dynamic RF shimming, the proposed algorithm ensured high image SNR throughout the human brain, compared with near‐complete local signal loss by the conventional magnitude‐least‐squares algorithm. Conclusion: Using finite‐difference regularization to avoid unwanted solutions, the robustness of RF shimming and small‐tip‐angle multispoke pulse design algorithms are improved, with better flip angle homogeneity and a monotonic trade‐off relationship between flip angle error and RF power.